Enhancing computational thinking in elementary students through STEM and Mojobot - Parinya Ruangtip; Thitichai Ruckbumrung; Wichien Rueboon (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study aims to explore the effects of using Mojobot, an interactive coding robot, within science, technology, engineering, and mathematics (STEM) education to enhance computational thinking (CT) skills among elementary school students. This research explores how educational robotics enhance algorithmic thinking, logical reasoning, and problem decomposition in young learners, addressing future workforce demands for digital literacy and problem-solving. Utilizing a quasi-experimental design with pre-test and post-test measured. The design involved a between-subject experimental group of seventy-four elementary students who were randomly assigned to an experiment (n=37) and a control group (n=37), the latter only receiving traditional STEM instruction without robotics. Students were given a pre-test and post-test to measure their algorithmic thinking, logical reasoning, and problem decomposition skills. Data were investigated using paired-samples t-tests and a 2-way analysis of variance (ANOVA). Outcomes revealed that both groups significantly improved CT skills, but the experimental group (M=28.56) improved significantly more than the control group (M=20.09) with a very large effect size (ES), respectively. The study found that a novel teaching method using Mojobot in STEM education enhances elementary students’ CT skills and supports 21st century skill development through robotics.